Are The Profitability of Companies Influenced by Working Capital and Liquidity? - Ramon Arthur Ferry Tumiwa; Nova Christian Mamuaya (AIBPM Publisher, 2018)
The purpose of our study is to examine and analyze: (1) the effect of working capital on profitability, (2) the effect of liquidity on profitability, and (3) the effect of working capital and liquidity simultaneously to profitability. This research was conducted at the ceramics, glass, and porcelain of manufacturing companies that listed on the Indonesia Stock Exchange (IDX) 2012-2016. The companies analyzed amounted to 6 companies determined based on sampling criteria. The analysis method used is panel data analysis by using Eviews 10 programming computer. The results of this study found that working capital has an insignificant relationship with profitability. The liquidity has an insignificant with profitability. The working capital and liquidity have no significant effect on profitability, simultaneous. Keywords: Working Capital, Liquidity, Profitability, Manufacturing Companies, Indonesia Stock Exchange